Comparison of Evolutionary Computation and Empirical Penman-Monteith Equation for Daily and Monthly Reference Evapotranspiration Estimation in Tropical Region - Mohd Samsuri, Saiful Farhan; Ahmad, Robiah; Zakaria, Mohd Zakimi (International Journal of Integrated Engineering, 2018)
Evapotranspiration is the combination of evaporation and transpiration processes that give means the process of water loss to the atmosphere. Reference evapotranspiration (ETo) estimation is part of water cycle that importance for planning and management of irrigation purposes and water resource systems. Due to its importance, the accurate modeling of ETo is of vital importance to estimate crop water requirement and its availability. This research presents a system identification and differential evolution approach by using Differential Evolution and System Identification (DESI) and Modified Genetic Algorithm (MGA) approach for modeling daily and monthly ETo in peninsular of Malaysia. The data set comprising air temperature, humidity, wind speed, and solar radiation was utilized for estimating ETo using FAO56 Penman Monteith (PM) equation as the reference. The modeling results were analyzed and compared with the traditional Penman Monteith method. Based on the analyses, the approach used was found that the models of ETo is adequate and understandable, and suited to estimate the dynamics of the evapotranspiration process. The performance of the model is comparable with that of the PM method.